ANALISIS RASIO TERHADAP LAPORAN KEUANGAN PADA PT. POLYCHEM INDONESIA TBK - Dewi Apriyani; Dhea Risa Faradilla; Dimas Abiyu Zakky; M. Thoha Ainun Najib (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2024)
This research focuses on the financial analysis of PT Polychem Indonesia Tbk, a company engaged in the manufacture of polyester and chemicals. In this analysis, various financial ratios are used, including liquidity, solvency, activity and profitability ratios. The results show that in 2022, the company's liquidity ratio is higher than the industry average, but in 2023, the company's quick and cash ratios are lower than the industry average. The company's solvency ratio also shows that the company still has a fairly high level of debt, which makes it difficult to Overall, the analysis results show that PT Polychem Indonesia Tbk still has several financial problems that need to be corrected to improve its performance.